2003
DOI: 10.5194/angeo-21-1359-2003
|View full text |Cite
|
Sign up to set email alerts
|

Charge-sign dependent modulation in the heliosphere over a 22-year cycle

Abstract: Abstract.A time-dependent model based on a numerical solution of Parker's transport equation is used to model the modulation of cosmic ray protons, electrons and helium for full 11-year and 22-year modulation cycles using a compound approach. This approach incorporates the concept of propagating diffusion barriers based on global increases in the heliospheric magnetic field as they propagate from the Sun throughout the heliosphere, combined with gradient, curvature and current sheet drifts and the other basic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
25
0

Year Published

2004
2004
2011
2011

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 33 publications
(26 citation statements)
references
References 48 publications
1
25
0
Order By: Relevance
“…Galactic comic electrons also show this 22-yr cycle and, having the opposite charge q, the drift theory predicts that this should be in antiphase with the nucleon GCR variation (Evenson, 1998). Measurements of 2.5 GV protons and electrons during the first fast latitudinal scan (1994.7-1995.6) revealed a small but clear latitudinal gradient in the time series not observed in the electron data (Heber et al, 1999) and in agreement with a drift-mode according to Ferreira et al (2003) (where protons are expected to drift in from the poles during these years of A>0). In the same paper Heber et al showed that between 1995.5 and 1998 the electron time series presented greater sensitivity to variations in the tilt of the HCS than the proton time series in agreement with negative particles propagating inward along the current sheet (Heber et al, 1999).…”
Section: The 22-year Periodicitymentioning
confidence: 63%
See 2 more Smart Citations
“…Galactic comic electrons also show this 22-yr cycle and, having the opposite charge q, the drift theory predicts that this should be in antiphase with the nucleon GCR variation (Evenson, 1998). Measurements of 2.5 GV protons and electrons during the first fast latitudinal scan (1994.7-1995.6) revealed a small but clear latitudinal gradient in the time series not observed in the electron data (Heber et al, 1999) and in agreement with a drift-mode according to Ferreira et al (2003) (where protons are expected to drift in from the poles during these years of A>0). In the same paper Heber et al showed that between 1995.5 and 1998 the electron time series presented greater sensitivity to variations in the tilt of the HCS than the proton time series in agreement with negative particles propagating inward along the current sheet (Heber et al, 1999).…”
Section: The 22-year Periodicitymentioning
confidence: 63%
“…This is true during most of the solar cycle phases of both magnetic field polarities and could point to a more significant role of the open solar flux in cosmic ray flux modulation than has been attributed to date. We notice an interesting fact, that is, the alternate peaked and rounded maxima seen in the neutron GCR flux time series (giving a 22-year cycle), successfully attributed to the polarity-dependent drift component of the propagation mechanisms of cosmic rays in the heliosphere (see Heber, 2000;Ferreira et al, 2003), is also seen in the variation of the two 1-AU open flux estimates presented here. This implies that the Sun has, as well as a twenty-two-year cycle in the direction of its dipolar field, a twenty-two-year pattern in the quantity of open field lines threading a sphere passing at 1 AU.…”
Section: Discussionmentioning
confidence: 76%
See 1 more Smart Citation
“…As a reference, these ratios are compared to the corresponding LIS ratios at 120 AU. For a review of the modeling of e À /p over 22 yr without a TS and observations with the Ulysses spacecraft, see Ferreira et al (2003) and Heber et al (2002Heber et al ( , 2003, respectively. Figure 6 is similar to Figure 5, except that the intensity ratios are shown at the TS (r s ¼ 90 AU).…”
Section: Modeling Resultsmentioning
confidence: 99%
“…Concerning modulation mechanisms, large-scale gradient, curvature and current sheet drifts that charged particles experience in the global heliospheric magnetic (HMF) are most prominent, if not the dominating mechanism at solar minimum, at least for charged nuclei. Drift models predict, apart from a clear charge-sign dependence Ferreira et al, 2003), different spectra for sequential solar minima based on the polarity of the solar magnetic field (Reinecke and Potgieter, 1994). For recent reviews on heliospheric modulation, see Potgieter et al (2001);Heber (2001);Zhang (2003);and Ferreira and Potgieter (2004a).…”
Section: Introductionmentioning
confidence: 99%